Research progress on the role of cold-sensitive channel TRPM8 in controlling low temperature-induced bone metabolic imbalance - Zhang Yimeng; Kazakova E. V; Chai Huijuan; Zhou Ping (Frigid Zone Medicine, 2023)
With increasing aging population, osteoporosis has emerged as a public health problem worldwide. Epidemiological data reveal that the prevalence of osteoporosis in cold regions is high, and low temperatures may crucially affect bone mass. Recent studies have found that the transient receptor potential melastatin-8 (TRPM8) channel, a cold-sensitive ion channel, can sense cold environment, and can be activated in cold environment. It may play an antagonistic role in low temperature-induced bone mass reduction. Mechanistically, this function may be ascribed to the activation of TRPM8 channel proteins in human bone marrow mesenchymal stem cells (hBM-MSCs), which causes osteoblast differentiation and mineralization in the bone. TRPM8 channel on the surface of brown adipocytes participates in the thermogenesis in brown adipose tissue (BAT) and the regulation of whole-body energy balance to maintain bone homeostasis. TRPM8 may be involved in bone remodeling throughout life. This paper reviews recent research on the possible antagonistic mechanism of TRPM8 in signaling pathways related to low temperature-induced bone mass loss and assesses the possibility of TRPM8 as a molecular target for the prevention and treatment of low temperature-induced osteoporosis in cold regions.